Prevalence of Febrile Seizures in School-Aged Children: A Community Based Survey in İzmir, Turkey - Merve Ateşoğlu; Tolga İnce; Duygu Lüleci; Alp Ergör; Adem Aydın (Journal of Pediatric Research, 2018)

(untitled)
Aim:Febrile seizures (FS) are the most common seizures seen in childhood. Although they are usually benign and self-limiting, parents feel great fear and concern about them. The prevalence of FS varies in different parts of the world. These differences are thought to be due to genetic, geographic and environmental factors. However, there has been no recent study about the prevalence of FS among Turkish children. This study was designed to find out the prevalence, clinical and some epidemiological features of FS among Turkish school children.Materials and Methods:A school based, cross-sectional study was conducted in first and second grade children. A stratified cluster sampling technique was used to define the study population, which represents the schools located in the metropolitan area of İzmir. Data were collected through a standard questionnaire from the parents who agreed to be involved in the study. The survey had questions about some demographic features of the children and FS episodes.Results:Three thousand eighty hundred six children and parent pairs agreed to participate in the survey. The FS prevalence determined was 4.8% (boys, 5.2%; girls, 4.3%, p>0.05). It was found that 28.5% of the children experienced their first FS between the ages of 18 months and three years old and most of them had an upper respiratory tract infection. The most common practice by parents during the seizure was admission to the nearest emergency room. The recurrence rate for FS was 33.0%.Conclusions:The FS prevalence determined in our study is lower than previous studies in Turkey. It was thought that the advancing healthcare systems in our country might have decreased the FS prevalence within the last eight years in Izmir.